2016
DOI: 10.1097/nne.0000000000000251
|View full text |Cite
|
Sign up to set email alerts
|

Supports and Barriers to Successful Progression in a DNP Program

Abstract: This study examined the supports, barriers, and strategies to successful progression in a DNP program using a nationwide online survey of DNP students and graduates. Subjects (n = 172) had a mean age of 46.2 years; 83% worked full time. Major barriers were competing demands of work, family, and school. Perseverance was a key element in overcoming barriers; most students reported being overwhelmed, and 37% considered quitting. Mechanisms for programs to consider in addressing this stress are discussed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
13
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 20 publications
1
13
0
Order By: Relevance
“…This study revealed that family includes not only nuclear family members but friends, coworkers, and student/peer groups as well, indicating social support may come from various sources (Dabney & Tai, 2013). Similar to previous studies (Cohen, 2011;Hlabse et al, 2016;Volkert et al, 2018), family was found to be mostly supportive. Where support was lacking, it reflected a misunderstanding of time commitment and perceptions of the value of a doctoral degree.…”
Section: Discussionsupporting
confidence: 85%
See 4 more Smart Citations
“…This study revealed that family includes not only nuclear family members but friends, coworkers, and student/peer groups as well, indicating social support may come from various sources (Dabney & Tai, 2013). Similar to previous studies (Cohen, 2011;Hlabse et al, 2016;Volkert et al, 2018), family was found to be mostly supportive. Where support was lacking, it reflected a misunderstanding of time commitment and perceptions of the value of a doctoral degree.…”
Section: Discussionsupporting
confidence: 85%
“…While previous research has shown family support significantly influences doctoral student success (Cohen, 2011;Hlabse et al, 2016;Volkert et al, 2018), this study helps to clarify how family support and lack of family support manifest. Doctoral students who experienced family support expressed family support in terms of social support (e.g., unconditional love, motivation) as opposed to financial and other types of support.…”
Section: Discussionmentioning
confidence: 84%
See 3 more Smart Citations